1989
DOI: 10.2307/3430784
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Adducts with Rat Nucleic Acids and Proteins: Dose-Response Relationship after Treatment In Vivo

Abstract: The dose-response relationship of the benzene covalent interaction with biological macromolecules from rat organs was studied. The administered dose range was 3.6 x 107 starting from the highest dosage employed, 486 mg/kg, which is oncogenic for rodents, and included low and very low dosages. The present study was initially performed with tritium-labeled benzene, administered by IP injection. In order to exclude the possibility that part of the detected radioactivity was due to tritium incorporated into DNA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
6
1
Order By: Relevance
“…Rothman, et al (1995) used the glycophorin A (GPA) gene loss mutation assay to assess the nature of DNA damage in workers heavily exposed to benzene. The GPA assay measures the frequency of variant cells that have lost the Arfellini, et al (1985), Creek, et al (1997), Mani, et al (1999), Turteltaub and Mani (2003) Rat (bone marrow) DNA adducts + Arfellini, et al (1985), Creek, et al (1997), Lévay, et al (1996), Pathak, et al (1995, Turteltaub and Mani (2003) Rat (liver) DNA adducts + Arfellini, et al (1985), Creek, et al (1997), Lutz and Schlatter (1977), Mani, et al (1999), Mazzullo, et al (1989), Turteltaub and Mani (2003) Rothman, et al (1995) reported a significant increase in the frequency of NN cells in benzene-exposed workers (compared with unexposed control subjects) in the absence of a significant effect on the frequency of NØ cells. These results suggest that benzene induces gene duplicating, but not geneinactivating, mutations at the GPA locus in benzene-exposed humans.…”
Section: Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rothman, et al (1995) used the glycophorin A (GPA) gene loss mutation assay to assess the nature of DNA damage in workers heavily exposed to benzene. The GPA assay measures the frequency of variant cells that have lost the Arfellini, et al (1985), Creek, et al (1997), Mani, et al (1999), Turteltaub and Mani (2003) Rat (bone marrow) DNA adducts + Arfellini, et al (1985), Creek, et al (1997), Lévay, et al (1996), Pathak, et al (1995, Turteltaub and Mani (2003) Rat (liver) DNA adducts + Arfellini, et al (1985), Creek, et al (1997), Lutz and Schlatter (1977), Mani, et al (1999), Mazzullo, et al (1989), Turteltaub and Mani (2003) Rothman, et al (1995) reported a significant increase in the frequency of NN cells in benzene-exposed workers (compared with unexposed control subjects) in the absence of a significant effect on the frequency of NØ cells. These results suggest that benzene induces gene duplicating, but not geneinactivating, mutations at the GPA locus in benzene-exposed humans.…”
Section: Genotoxicitymentioning
confidence: 99%
“…In addition to oral and inhalation routes, many researchers tested subcutaneous and intraperitoneal routes as well; the results for these alternate routes of exposure were largely positive for chromosomal aberrations in bone marrow (Anderson and Richardson, 1981;Speck, 1972, 1973;Kolachana, et al, 1993;Meyne and Legator, 1980;Philip and Jensen, 1970), micronuclei in bone marrow (Diaz, et al, 1980), and sister chromatid exchange in mouse fetus liver cells (Sharma, et al, 1985). Binding of benzene and/or its metabolites to DNA, RNA, and proteins has been consistently observed in rats and mice (Arfellini, et al, 1985;Creek, et al, 1997;Lévay, et al, 1996;Mani, et al, 1999;Mazzullo, et al, 1989;Turteltaub and Mani, 2003). Arfellini, et al (1985) noted that binding to RNA and proteins was more prevalent than binding to DNA.…”
Section: Genotoxicitymentioning
confidence: 99%
“…It is likely that this will focus on the measurement of adduct compounds formed by covalent bonding between DNA and benzene metabolites as part of the process of genetic damage by the latter. [105][106][107] Adducts of unique structure are formed by many carcinogens in interaction with DNA and their levels within tissues reflect a combination of a subject's exposure and the subject's metabolic capacity to generate the genotoxic metabolites. 108 They are believed to undergo repair with time, leading to a gradual diminution in their number, the rate being dependent on the nature of the carcinogen and its site of adduct formation within DNA.…”
Section: Biomonitoring Of Benzene Exposurementioning
confidence: 99%
“…In contrast to these in vitro findings, evidence for the formation of DNA adducts in animals treated with benzene has been contradictory. Dose-dependent binding of radiolabeled benzene to DNA, RNA, and protein in various tissues of mice and rats has been reported (20)(21)(22). 32P-Postlabeling studies by Bauer et al (23) have demonstrated DNA adduct formation in the liver of rabbits treated with benzene; however, Reddy et al (24)(25)(26) were unable to detect the formation of DNA adducts in various tissues of either Sprague-Dawley rats or B6C3F1 mice administered benzene or its hydroxylated metabolites.…”
Section: Introductionmentioning
confidence: 99%